Planarized intramolecular charge transfer: a concept for fluorophores with both large stokes shifts and high fluorescence quantum yields - Haberhauer, Gebhard; Gleiter, Rolf; Burkhart, Christoph (Chemistry - a European journal, 2016)
Abstract Fluorophores were successfully used in several areas of chemistry and biochemistry. For many purposes, however, it is necessary that the fluorescence compound features a high fluorescence quantum yield as well as a large Stokes shift. The latter is, for example, achieved by the use of a twisted intramolecular charge-transfer (TICT) compound, which shows a twisted geometry in the excited state. However, the higher the twisting is, the lower becomes in general the fluorescence quantum yield as the resulting emission from the twisted state is forbidden. In order to escape this dilemma, we propose the model of planarized intramolecular charge-transfer (PLICT) states. These compounds are completely twisted in the ground states and planar in the excited states. By means of quantum chemical calculations (time-dependent (TD)-B3LYP and CC2) and experimental studies, we could demonstrate that 1-aminoindole and its derivatives form photoinduced PLICT states. They show both very large Stokes shifts ( =9000?13?500?cm?1, i.e., ?=100?150?nm) and high fluorescence quantum yields. These characteristics and their easy availability starting from the corresponding indoles, make them very attractive for the use as optical switches in various fields of chemistry as well as biological probes.
Gesehen am 02.09.2020